La luce nell’Empireo dantesco - Gagliardi, Mauro (Alpha Omega, 2011)
This article explores the theme of light in the final cantos of Dante’s Paradise, which describe the Empyrean. It goes to the research of the sources for the concept of Empyreal light expressed by Dante, and critically evaluates various hypotheses advanced by contemporary scholars with a particular focus on the Dantean integration between the representatives of the “metaphysics of light” following Plotinus. The synthetic character of Empyreal light developed by Dante emerges from the study. The conclusion reveals the possibility of further investigation in the work of Dante, that prominent figure of the Christian Middle Ages who made the search for a synthesis one of his principle reasons for study.